Inferior Venacaval Thrombosis in Active Tuberculosis - Momen, Abdul Basit Ibne; Twinkle, Furial Quraishi; Quraishi, Firoz Ahmed (Anwer Khan Modern Medical College Journal, 2020)
Approximately one third of the world's population is infected with Mycobacterium tuberculosis. TuberculosisJ has several mechanisms that induce a hypercoagulable state and can lead to thromboembolic complications. A variety of factors have been postulated to predispose patients with tuberculosis to venous thrombosis that include local stasis due to venous compression by lymph nodes and relative immobility caused by respiratory, alteration in coagulation factors and reactive thrombocytosis. Only a few case reports showing similar findings. We present a case, man of 26 years old, who presented deep vein thrombus of inferior vena cava from its origin extending up to the entrance of the liver revealed signal changes on L2 vertebrae and CT guided FNAC was negative for malignancy but suggestive of tuberculosis. There might be a possible association between deep venous thrombosis and use of Rifampicin but this does not contraindicate the use of Rifampicin but these patient may need close monitoring. AKMMC J 2020; 11(2) : 137-139